Semi-analytical orthotropic model for the prediction of the post-buckling behaviour of stiffened cylindrically curved steel panels under uniaxial compression. (January 2019) - Manco, Tiago; Martins, João Pedro; Rigueiro, Constança; Simões da Silva, Luís
Highlights: A semi-analytical method for the post-buckling behaviour of stiffened curved panels is proposed. The large deflection model accounts explicitly with the number and geometry of the stiffeners. The results obtained by the proposed procedure are compared with FEA yielding good results. Closed-form analytical expressions are derived based on SDOF approximations. Abstract: Stiffened curved steel panels are increasingly used in structural applications in civil, naval and offshore engineering. Due to the incorporation of stiffeners these elements are able to withstand substantial loads with low material usage. However, design provisions to predict the strength of these elements are practically non-existent. The aim of this paper is to present a robust semi-analytical procedure for the prediction of the post-buckling behaviour of stiffened cylindrically curved steel panels under uniform uniaxial compression. The semi-analytical procedure is based on an orthotropic model with the number and geometry of the stiffeners properly taken into account. The procedure is based on nonlinear stability models based on large deflection theory incorporating initial imperfections and geometric nonlinearity. The problem is solved and the equilibrium paths are obtained through the Rayleigh-Ritz method. The validity of these computational models is assessed with the results of finite element analyses for different curvatures, aspect ratios, number and geometry of stiffeners yielding good results. Finally, a design-oriented closed-form expression is derived for the second-order elastic behaviour of the stiffened panels.